2023
DOI: 10.3390/foods12061344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Composite Edible Coatings Combined with Modified Atmosphere Packaging on the Storage Quality and Microbiological Properties of Fresh-Cut Pineapple

Abstract: This study investigated the effect of edible coating (EC), modified atmosphere packaging (MAP), and edible coating + modified atmosphere packaging (EC + MAP) treatments on the quality of fresh-cut pineapples during storage at 4 °C. The quality differences were analyzed by measuring the quality, physiological indicators, and total microbial counts. After 8 d of storage, the brightness (L*) values of the EC + MAP and control samples were 72.76 and 60.83, respectively. The water loss and respiratory rate of the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…As illustrated in Figure 4B , the total phenolic content in all samples gradually increased due to the synthesis and accumulation of phenolic compounds induced by fresh-cut jackfruit wounds ( 52 ). Similar studies confirmed that fresh-cut strawberries ( 53 ) and fresh-cut pineapples ( 37 ) also showed an increasing trend during storage. During the whole storage period, the nisin+ε-PL treatment was always significantly higher than that of the single treatment (nisin or ε-PL) and CK group ( p < 0.05).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…As illustrated in Figure 4B , the total phenolic content in all samples gradually increased due to the synthesis and accumulation of phenolic compounds induced by fresh-cut jackfruit wounds ( 52 ). Similar studies confirmed that fresh-cut strawberries ( 53 ) and fresh-cut pineapples ( 37 ) also showed an increasing trend during storage. During the whole storage period, the nisin+ε-PL treatment was always significantly higher than that of the single treatment (nisin or ε-PL) and CK group ( p < 0.05).…”
Section: Resultssupporting
confidence: 76%
“…Studies have shown that fruit color change correlates with cell membrane semi-permeability. When the cell membrane is damaged, pigment material flows into the intercellular space along with intracellular fluids, altering the refractive index between the cell and its surrounding environment ( 37 ). In addition, enzymatic browning is the main factor causing browning in fresh-cut fruits and vegetables, and PPO and POD are key enzymes in enzymatic browning ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…The combination of MAP with ultrasound treatment is able to increase the preservation ability for meat products compared to individual treatments by inhibiting the growth of Pseudomonas and Carnobacterium bacteria and also maintaining the flavor of the meat 81) . In fruit products such as pineapples and apples, the combination of MAP and edible coating film can inhibit metabolism, which causes enzymatic browning 82,83) . In addition, edible coating film can also be used as an anti-microbial which will inhibit the growth of Gram-positive and Gramnegative bacteria 31,32) .…”
Section: Map Technology Developmentmentioning
confidence: 99%
“…The total microbial count of FCP at 8 days was 6.45 Log CFU/g. (Liao et al ., 2023). This leads to lower quality and shorter shelf life of pineapple, causing food loss in the life cycle of its food chain.…”
Section: Introductionmentioning
confidence: 99%